APAKAH GENDER MEMPENGARUHI PERILAKU KONSUMSI BERKELANJUTAN DALAM PERSPEKTIF COM-B? (STUDI KASUS PERILAKU MENGURANGI KONSUMSI DAGING) - Syarif, Hilmi Dzakwan; Fitria Dina Riana; Rachman Hartono (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
The global population is projected to reach 9.7 billion by 2050, increasing food demand and straining the environment. Meat consumption, responsible for 31% of global greenhouse gas emissions, drives deforestation, biodiversity loss, and climate change. Despite its environmental and health risks, global meat consumption is expected to rise by 76% by 2050. In Indonesia, while tempeh and tofu are cultural staples, plant-based protein consumption has declined, contradicting climate commitments under the Paris Agreement. This study analyzes meat consumption behavior among 384 Universitas Brawijaya students (18-25 years) using the COM-B model, focusing on capability, opportunity, and motivation. Significant gender differences emerged in capability (e.g., cooking skills and environmental awareness), opportunity (e.g, habit consumption and sosio environtmrntal),and motivation (e.g., males’ preference for meat, driven by masculinity traits). Key barriers include taste and habitual meat consumption, while opportunities involve affordability and interest in healthy food. Effective strategies include improving plant-based meat appeal, providing information on meat’s harmful effects, and offering affordable alternatives. Gender-tailored interventions addressing motivations and capabilities are essential to promote plant-based protein adoption and reduce meat consumption. Keywords: Behavior change, reducing meat consumption, plant-based protein alternatives, and young adulthood